Investigating causes of self-burning in married women - F Amirmoradi; A.M Memari; T Ramim; A Mehran; Kh Khosravi (Tehran University of Medical Sciences, 2005)
Introduction: Self-burning is a cruel method of suicide and prevention is the most effective way to decrease its morbidity and mortality. Material and Methods: This investigation is a descriptive prospective study performed at Shahid Motahari Burn Center, Tehran, Iran from December 2001 to December 2002. Inclusion criteria included being female, married, having no history of medical and mental disorders and admission of self-burning. Data were collected by a questionnaire and interviews and were analyzed with descriptive statistics methods and chi-square test.            Results: A total of 35 cases entered our study. The mean age of patients was 24.573.94 years and 48.6% of cases were in the 21-25 year age group, 80% had primary school education, 97.1% were housekeeper and 68.8% had low economical status. There were statistically significant differences in all of these variables. In 42.9% self-burning had happened at 12-18 hour period and in 45.7% it had occurred at yard. Kerosene had been used by 91.4% of the women as the burning agent 94.3% of the women had experienced husband's violence (verbal and physical), 60% of the women stated that their husbands were guilty in their action and 91.4% of the women didn't know any supportive sources in the society. The mortality rate was 100%. Conclusion: This research showed that family violence and marital problems are the most important causes of self-burning in the married women. Because of close relationship to families, community health nurses can prevent self-burning in married women by detecting and eliminating these risk factors.